Hybrid perfluorocarbon/carboxylic acid thin films via plasma deposition of hexafluoropropene and acrylic acid mixtures. (February 2021) - Bosso, P.; Milella, A.; Armenise, V.; Fanelli, F.; Fracassi, F.
Abstract: Polymeric films containing hydrophilic and hydrophobic functionalities are of interest for several applications, from biomaterials to fuel cells. In this study, we report on the plasma copolymerization of hexafluoropropene - acrylic acid mixtures. By finely tuning the monomers' ratio and the plasma power, it is possible to adjust the relative amount of the hydrophilic and hydrophobic functionalities in the deposited films. Correspondingly, the wetting behavior can be tuned from fully hydrophilic to hydrophobic. Finally, depending on the process parameters, film proton conductivities in the range 20–70 mS cm −1 are obtained. Highlights: Polymeric films deposited by plasma copolymerization of hexafluoropropene - acrylic acid mixtures. The relative amount of hydrophilic and hydrophobic functionalities tuned by the monomers' ratio and RF plasma power. Film wetting behavior tuned from fully hydrophilic to hydrophobic and proton conductivity from 20 to 70 mS cm -1 .